Effect of the DASH-diet and salt Kardisal® on blood pressure in adolescents with prehypertension (Cooperative multicentre interventional study) - Janda, Jan; Veleminsky, Milos; Sulakova, Terezie; Prochazka, Bohuslav; Eliasek, Jan; Stránský, Pravoslav; Rokyta, Richard (Neuro-endocrinology letters, 2017)
BACKGROUND: In a cooperative multi-center interventional study of 60 probands with prehypertension and normal BMIs were followed for 3 months. DESIGN: The intervention included the DASH diet for 3 months in 30 probands plus sodium limited intake using the low sodium salt Kardisal® (60% NaCl, 40% KCl) (group A) and the DASH diet for 3 months in 30 probands without Kardisal® (group B). RESULTS: In group A (n=26 probands evaluated) the systolic blood pressure (median) decreased significantly from 138 to 129 mmHg (p<0.001), while the diastolic blood pressure had a statistically non-significant decrease. In group B (n=25 probands evaluated) the SBP decreased significantly from 135 to 132 mmHg (p<0.001), and the DBP decreased significantly from 85 to 69 mmHg (p<0.001). CONCLUSION: Despite a relatively short period on the DASH diet, the intervention produced a significant decrease in the blood pressure of prehypertensive adolescents. The additional use of a low sodium salt for home cooking was not found to have any advantages over the DASH diet alone.
Keywords: Dietary Approaches To Stop Hypertension; dospělí; Diet, Sodium-Restricted; ženské pohlaví; mladiství; dieta s nízkým obsahem soli; lidé; ambulantní monitorování krevního tlaku; pilotní projekty; mladý dospělý; prehypertenze; Prehypertension; Humans; DASH dieta; mužské pohlaví; Adult; Blood Pressure Monitoring, Ambulatory; Male; Pilot Projects; Young Adult; Blood Pressure; Adolescent; krevní tlak; Female